Penyelenggarakan School Based Inset Sebagai Upaya Peningkatan Profesionalisme Guru dalam Kegiatan Belajar Mengajar di SDNo.75/IX Muaro Kumpeh Tahun Pelajaran 2019 / 2020 - Dameri Situmeang (Peneliti.net, 2020)
This research is supported by: 1) For the work of teachers in carrying out teaching and learning activities is very varied and the quality of the teacher varies. 2) The progress and development of science and technology (IPTEK) requires adjustment and professional development of teachers to be able to develop education in schools. 3) Ministerial Decree: Number 84/2002 regarding professional positions and credit figures requires teachers to further improve their professional abilities, work, excel in carrying out their daily school duties. 4) The natural conditions of Indonesia require a communication system and professional development of teachers by using multi dimensional. From the above background, the writer conducted a research entitled